The Contribution of Caliph Abu Bakar As-Shidiq at the Beginning of the Caliphate of Rashidah - Purwanto, Ari; Mufid, Abdul (East Asian Journal of Multidisciplinary Research, 2024)
This research describes Islamic leadership under Caliph Abu Bakar As-Shidiq. The focus of this research is to show the successes achieved by Caliph Abu Bakar during the 2 years and 3 months he led. By using library research methods, namely researchers search for, study and understand literature related to Caliph Abu Bakar As-Shidiq, the leadership of Caliph Abu Bakar As-Shidiq. Researchers looked for general data about Caliph Abu Bakar As-Shidiq to find out his biography. Researchers studied in more detail and explored data on the leadership policies of Caliph Abu Bakar As-Shidiq and what were the contributions of Caliph Abu Bakar As-Shidiq in Islamic da'wah. So the author found that in a short time, he crushed the apostates who claimed to be false prophets and people who denied zakat and prayer.